Exploring the Comprehensibility of Ten Different Musical Notation Systems and Underlying Factors - Siyao Cheng; Andrew J. Milne; Roger T. Dean; José Hanham; Jennifer MacRitchie (Music & Science)
Numerous systems of musical notation have been developed to address some of the complexities associated with conventional Staff notation, such as translating it into physical movements and memorizing the meaning of its symbols. Surprisingly, there has been little empirical research assessing and comparing the comprehensibility of conventional versus alternative notation methods. In this study, three main features were assessed for 10 different musical notation systems: discriminability (the ease of visually distinguishing pitch or duration changes in notation), iconicity (extent of resemblance between melodies and notation), and complexity . A total of 213 valid responses were collected in an online experiment. Participants completed two tasks, visual discriminability and melody-notation matching. They also provided complexity ratings for different notational systems. Multilevel Bayesian regression models show strong evidence that Figurenotes, Numbered notation, and Piano Roll notation have a relatively high level of discriminability, while Figurenotes, Proportional notation, Staff notation, and Piano Roll notation have a relatively high level of iconicity. Piano Roll notation was rated the least complex musical notation system. Differences in the results across pitch and duration dimensions, age, and musical sophistication were also found. Importantly, we also examined the effects of the different visual variables used by the notational systems (color, position, shape): changes in position have the highest discriminability, iconicity, and the lowest complexity. Qualitative analysis for some open questions also supported Piano Roll notation as being the most favorable musical notation, especially among novices.